Etude de l'addition de sufactifs non ioniques sur les melanges eau-huile hydrocarbonée - DJENONTIN, TINDO SÉBASTIEN; AVLESSI, FÉLICIEN; DANGOU SOSSOU, JUSTINE; ACCROMBESSI, COFFI GEORGES; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2003)
n this paper the phase diagrams for the ternary systems TX114-Water–Dodecane, TN101-Dodecane have been characterized and the structure of the liquid crystalline phase surfactant water have been studied by polarizing microscopy and X-ray diffraction. Those studies have shown that liquid crystalline phase has a hexagonal structure.
Keywords: surfactant; liquid crystalline phase; phase diagrams; emulsion; X-ray diffraction.